The Civil Suit for International Disputes before the International Court of Justice : Analytical Study - Adnan Abdullah Rasheed; Zainab Ahmad Alani (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The international community has always been keen to find ways to resolve conflicts and reach solutions, to resolve international conflicts that sometimes leave victims estimated at millions of people. To create a permanent international court to resolve international disputes, especially after the damage that afflicted humanity after the First World War, Countries established the League of Nations as the first permanent international organization in parallel with the establishment of the Permanent Court of International Justice as its judicial institution. Nevertheless, the failure of the League of Nations to maintain international peace and security because of the outbreak of World War II, a new international organization was established to replace the League of Nations, the United Nations, and its judicial organ is the International Court of Justice, which replaced the Permanent Court of International Justice. The International Court of Justice has two main jurisdictions: judicial and advisory. The civil lawsuit is a judicial means to protect the rights of states in this court result of disputes that erupt between states because of conflicting interests, and these disputes threaten international peace and security, which necessitates the intervention of the international judiciary to resolve them.